An Investigation into Domestic Water Consumption Patterns in Iten Town, Kenya - Ngetich, M. J.; Kiplagat, A. K.; Ng’etich, J. (Africa Environmental Review Journal, 2022)
Scarcity of freshwater has become one of the major challenges facing urban areas. With ever-increasing urban population, the demand for water has gone up with little or no expansion of the existing water supply systems to match the growing demand. In that regard, this study sought to investigate domestic water consumption patterns in Iten Town, Kenya in a bid to understand more about urban freshwater scarcity. The study employed a descriptive survey design incorporating both quantitative and qualitative approaches. Structured questionnaires were distributed to 200 randomly selected households. The findings revealed that the per capita domestic water demand in Iten town stands at 44 litres, which was comparatively lower than the recommended WHO standard of 50 litres. Piped water was the main source of water (51.3%) with approximately 21-40 liters used per day (l/p/d) in laundry. At 64 l/p/d, findings revealed that households with fewer members used more water per person per day on average than, for example, a 8 member household that used 27 l/p/d. This study recommends practice of “7 R’s” approach as a guide in reducing the consumption of fresh water resources.